Transnational Korean Television: Cultural Storytelling and Digital Audiences - Ju, Hyejung (Transnational Communication and Critical/Cultural Studies, 2020)
Transnational Korean Television: Cultural Storytelling and Digital Audience provides previously absent analyses of Korean TV dramas' transnational influences, peculiar production features, distribution, and consumption to enrich the contextual understanding of Korean TV's transcultural mobility. Even as academic discussions about the Korean Wave have heated up, Korean television studies from transnational viewpoints often lack in-depth analysis and overlook the recently extended flow of Korean television beyond Asia. This book illustrates the ecology of Korean television along with the Korean Wave for the past two decades in order to showcase Korean TV dramas' international mobility and its constant expansion with the different Western television and their audiences. Korean TV dramas' mobility in crossing borders has been seen in both transnational and transcultural flows, and the book opens up the potential to observe the constant flow of Korean television content in new places, peoples, manners, and platforms around the world. Scholars of media studies, communication, cultural studies, and Asian studies will find this book especially useful.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Media Reform and Civil Society in ‘Amazing Thailand’ - Lewis, Glen (Television, Regulation and Civil Society in Asia, 2002)
The reform of media regulation can be read as part of the wider movement towards democratisation in Thailand in the 1990s. Real progress was made in media reform, yet as the traditional control of the Army has been reduced, the power of commercial media monopolies has grown. The main threat to further media liberalisation is now the growth of private monopolies. This was exemplified by the election of Thaksin Shinawatra in January 2001, as he is a media magnate on an international scale comparable with Italy’s Silvio Berlusconi. Both men have used their communications business as a path to political power. The first part of this chapter will summarise Thai ideas about civil society, television regulation and the political context of media reform, followed by an analysis of how civil society issues are represented on Thai TV. Broadly, there are urban news and current affairs programmes of an investigative nature, and then there are rural-oriented programmes featuring community participation, notably Lan Ban Lan Muang. Finally, the prospects for media regulation since Thaksin’s election will be considered. The progress towards media reform made in the second half of the 1990s has since stalled under Thaksin’s new government.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Thaïlande (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television in Post-Reform China: Serial Dramas, Confucian Leadership and the Global Television Market - Zhu, Ying (Routledge, 2008)
This book explores the political, economic, and cultural forces, locally and globally that have shaped the evolution of Chinese primetime television dramas, and the way that these dramas in turn have actively engaged in the major intellectual and policy debates concerning the path, steps, and speed of China’s economic and political modernization during the post-Deng Xiaoping era. It intertwines the evolution of Chinese television drama particularly with the ascendance of the Chinese New Left that favors a recentralization of state authority and an alternative path towards China’s modernization and China’s current administration’s call for building a "harmonious society." Two types of serial drama are highlighted in this regard, the politically provocative dynasty drama and the culturally ambiguous domestic drama. The book also provides cross-cultural comparisons that parallel the textual and institutional strategies of transnational Chinese language TV dramas with dramas from the three leading centers of transnational television production, the US, Brazil and Mexico in Latin America, and the Korean-led East Asia region. The comparison reveals creative connections while it also explores how the emergence of a Chinese cultural-linguistic market, together with other cultural-linguistic markets, complicates the power dynamics of global cultural flows.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Television of Intervention: Mediating Patron–Client Ties in the Philippines - Corpus Ong, Jonathan (Television Histories in Asia: Issues and Contexts, 2015)
Similar to the other countries discussed in this volume, elite dominance over mass media has been a main characteristic of Filipino history. Foreign-educated Filipino intellectuals from wealthy families founded the early periodicals that demanded reform and/or independence from Spanish colonization in the late nineteenth century (Anderson 1983 ). Today, ‘old rich’ landowning families own and operate television networks, radio stations, and newspapers not only as part of prestigious and profi table media conglomerates, but also in connection with their interests in industries as varied as oil and agriculture to insurance, shipping, and mining.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Philippines (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Working Women and Romance on Japanese Television Dramas: Changes since Tokyo Love Story - Freedman, Alisa (Television Histories in Asia: Issues and Contexts, 2015)
Since their development in their current format in the early 1990s as a means to attract female viewers in their twenties, Japanese prime-time television dramas-known commonly as ‘ dorama ’ 1 —have featured working women. Even police procedurals, medical dramas, and serials based on ‘ shojo manga ’ (graphic novels for girls) depict women working outside the home. The dorama most watched by Japanese audiences older than age 25, and those that continue to attract global fans, present the daily lives of independent women working in Tokyo. The protagonists enact fantasies about female professionals while depicting real issues facing the larger generations they represent. Viewers may not want to be these characters, but they can see aspects of themselves in them.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Trust and Television in Globalizing India - McMillin, Divya (Television Histories in Asia: Issues and Contexts, 2015)
Writing a history of Indian television immediately begs the question, how do we want it read? Exhaustive chronological treatments anchor the field (Kumar 2000 ), ideological examinations reveal a Hindu-centric nation with serious consequences for religious and gender minorities (Rajagopal 1996 ; Mitra 1993 ; Van der Veer 1997 ), development analyses demonstrate the failures of a socialist state (F ü risch and Shrikhande 2007 ), and audience studies reveal complex negotiations among multiple identity positions (Mankekar 1999 ). These critical approaches to the study of television in India rightly expose power differentials that facilitate, through the centuries, the inequities of interwoven structures of imperialism, colonialism, casteism, and capitalist patriarchy. Most importantly, they highlight the chronic condition of distrust in postcolonial societies, making it highly challenging to legitimize profi table connections to global circuits as they modernize under the very conditions that once constrained them.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Reality Television and the Making of Mobile Publics: The Case of Indian Idol - Punathambekar, Aswin (The Politics of Reality Television: Global Perspectives, 2010)
In the summer of 2007, media coverage of Indian Idol-3 focused attention on how people in the Northeast Indian state of Meghalaya cast aside decades-old separatist identities to mobilize support for Amit Paul, a ﬁnalist from the region. While some fans set up websites and blogs to generate interest and support from the rest of the country and abroad, others formed a fan club and facilitated eﬀorts by a range of groups and organizations to sponsor and manage PCOs (public call oﬃces) in diﬀerent parts of Meghalaya, distribute pre-paid mobile phone cards, and set up landline voting booths. Recognizing the ways in which these activities were beginning to transcend long-standing ethnic, religious, linguistic, and spatial boundaries, state legislators and other politicians soon joined the eﬀort to garner votes for Amit Paul, with the chief minister D. D. Lapang declaring Amit Paul to be Meghalaya’s “brand Ambassador for peace, communal harmony and excellence.”1 It seemed that this three-month-long campaign around a reality television program could set the stage for a remarkable refashioning of the socio-cultural and political terrain in Meghalaya. As one commentator remarked:When Meghalaya’s history is written, it could well be divided into two distinct phases – one before the third Indian Idol contest and one after it. A deep tribal-non-tribal divide, punctuated by killings, riots, and attempts at ethnic cleansing, would mark the ﬁrst phase. A return to harmony and to the cosmopolitan ethos of the past would signify the second. The agent of change: Amit Paul, the ﬁnalist of the musical talent hunt on a TV channel.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Big Brother, Bigg Boss: Reality Television as Global Form - Sen, Biswarup (Channeling Cultures: Television Studies from India, 2014)
This chapter looks at one well-known format in reality television– Big Brother (Bigg Boss in India) – in order to shed light on the complicated relationship between the forces of globalization, national and local cultural formations and the dictates of commercially driven entertainment. It analyses the essential features of format television to argue that the very mode of its constitution as an economic and aesthetic object inclines it towards the global. The chapter elucidates the reality behind global cultural formations by discussing the two main theoretical approaches to the question of global culture – cultural imperialism and cultural globalization. It also offers some speculations about how reality television embodies global form and thus functions as a sort of “Bigg Boss” that dictates contemporary modes of meaningful behaviour.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Spaces of Television: Rethinking the Public/Private Divide in Postcolonial India - Kumar, Shanti (Channeling Cultures: Television Studies from India, 2014)
This chapter critically evaluates changing definitions of ‘public’ in Indian television in relation to discourses of globalization and media privatization. It examines the debate over the nationalist agenda of public broadcasting in India in relation to the demands for alternative models of broadcasting, and the rise of private commercial satellite channels since the 1990s. It also discusses how representations of traditionally private desires of sexuality and intimacy in soap operas, reality TV shows and music television are redefining the public in India. It outlines the ways in which private desire is made visible — and thus made public — through the convergence of the television screen, the cinematic screen, the computer screen, and the mobile screen. It argues that binaries of ‘public’ versus ‘private’ force us into either/or debates even though such category systems are always-already hybrid in postcolonial societies such as India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television, Narrative Identity, and Social Imaginaries: Hermeneutic Approach - Asthana, Sanjay (Channeling Cultures: Television Studies from India, 2014)
The chapter argues that Paul Ricouer’s hermeneutics offers a way forward in examining not only the ideological and narrative structures of television, but also particular modalities through which viewers appropriate and interpret televisual texts. To this end, the chapter shall sketch an analytic framework by bringing together Ricoeur’s hermeneutic philosophy, particularly his concepts of narrative identity and temporality, and the notion of social imaginaries developed by postcolonial theory in a productive dialogue. Ricoeur’s hermeneutics presents an understanding of the human subject in terms of an embodied subjectivity that takes us beyond singular conceptions of identity, whether in terms of the abstract Cartesian subject, or various other discourse-centred theorizations of subject. The chapter demonstrates that the notion of embodied subjectivity and social imaginaries enable a better grasp in examining the articulations of class, caste, gender, and religious identities on Indian television.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Televisual Temporalities and the Affective Organization of Everyday Life - Mankekar, Purnima (Channeling Cultures: Television Studies from India, 2014)
This chapter sketches a theoretical framework for analyzing the role of television in the temporal and affective organization of everyday life. Rather than engage an empirical analysis of the “impact” of television, the chapter aims to raise conceptual questions about how satellite television participates in the creation of regimes of affect and temporality. Diverging from theories of transnational media that foreground the ubiquity of spatiality, it proposes that we examine how duree and histoire, historical consciousness and the everyday are co-constructed through the affectivity of television. The chapter begins by examining the work of television news in the production of crisis; it analyses how television enables the formation of historical consciousness; and it points to the ways in which television participates in the creation of a sense of the everyday. It thus outlines some of the ways that we can theorize the centrality of television to the production of temporalities of historicity, contemporaneity, and futurity.
Keywords: 1-TV; 2-Approches sociologiques; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Romance in Post-Socialist Chinese Television - Wen, Huike (East Asian popular culture, 2020)
"Surveying the latest Chinese TV shows centered on romantic relationships, this book joins the expanding body of literature on the ever-evolving structures of feelings while breaking new grounds in media studies. With its thorough investigation of a wide range of genres, narratives, and public discourses, the volume makes timely and significant contributions to the fields of media studies, China studies, and the cultural history of love and romance."--Hui Faye Xiao, University of Kansas, USA "What does romantic love mean for Chinese people today? How is love represented in popular Chinese television programs? Huike Wens fascinating and important book explores how romantic love promises young Chinese urbanites individual freedom, fulfillment, and purpose in life, yet also plays an ideological role in creating social cohesion and maintaining traditional patriarchal values in post-socialist China. An entertaining and thought-provoking insight into how love functions in contemporary Chinese society." --Hsu-Ming Teo, Macquarie University, Australia This book examines how representations of romantic love in Chinese television programs reflect the contradictions inherent to changing dominant values in post-socialist Chinese mainstream culture. These representations celebrate individual freedom, passion, and gender equality, and promise change based on individual diligence and talent, while simultaneously obstructing the fulfillment of these ideals. Huike Wen is an Associate Professor at Willamette University (Salem, Oregon). Her research focuses on the intersection of genders, emotions, media technology, and nations in transnational Chinese and East Asian media and culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Television and the Modernization Ideal in 1980s China: Dazzling the Eyes - Wen, Huike (Lexington Books, 2013)
Television and the Modernization Ideal in 1980s China: Dazzling the Eyes explores Chinese television history in the pivotal decade of the 1980s and explains the intellectual reception of television in China during this time. While the Chinese media has often been a topic within studies of globalization and the global political economy, scholarly attention to the history of Chinese television requires a more extensive and critical view of the interaction between television and culture. Using theories of media technology, globalization, and gender studies supplemented by Chinese periodicals including Life Out of 8 Hours, Popular TV, Popular Cinema, Modern Family, and Chinese Advertising, as well as oral history interviews, this book re-examines how Western technology was introduced to and embedded into Chinese culture. Wen compares and analyzes television dramas produced in China and imported from other nations while examining the interaction between various ideologies of Chinese society and those of the international media. Moreover, she explores how the hybridity between Western television culture and Chinese traditions were represented in popular Chinese visual media, specifically the confusions and ambitions of modernization and the negotiation between tradition and modernity, nationalism and internationalism, in the intellectual reception of television in China.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Making of Exile Culture: Iranian Television in Los Angeles - Naficy, Hamid (University of Minnesota Press, 1993)
Naficy explores the seemingly contradictory way in which immigrant media and cultural productions serve as the source both of resistance and opposition to the domination by host and home country's social values while simultaneously serving as vehicles for personal and cultural transformation and assimilation of those values.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice PANDC; Iran (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

China Turned On: Television, Reform and Resistance - Lull, James (Taylor & Francis Group, 2013)
The years following the Cultural Revolution saw the arrival of television as part of China's effort to 'modernize' and open up to the West. Endorsed by the Deng Xiaoping regime as a 'bridge' between government and the people, television became at once the official mouthpiece of the Communist Party and the most popular form of entertainment for Chinese people living in the cities. But the authorities failed to realize the unmatched cultural power of television to inspire resistance to official ideologies, expectations, and lifestyles. The presence of television in the homes of the urban Chinese strikingly broadened the cultural and political awareness of its audience and provoked the people to imagine better ways of living as individuals, families, and as a nation. Originally published in 1991, set within the framework of China's political and economic environment in the modernization period, this insightful analysis is based on ethnographic data collected in China before and after the Tiananmen Square disaster. From interviews with leading Chinese television executives and nearly one hundred families in Beijing, Shanghai, Guangzhou, and Xian, the author outlays how Chinese television fosters opposition to the government through the work routines of media professionals, television imagery, and the role of critical, active audience members.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Chine (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Broadcasting Politics in Japan: NHK and Television News - Krauss, Ellis S. (Cornell University Press, 2018)
The aftermath of Japan's 1945 military defeat left its public institutions in a state of deep crisis; virtually every major source of state legitimacy was seriously damaged or wholly remade by the postwar occupation. Between 1960 and 1990, however, these institutions renewed their strength, taking on legitimacy that erased virtually all traces of their postwar instability.How did this transformation come about? This is the question Ellis S. Krauss ponders in Broadcasting Politics in Japan; his answer focuses on the role played by the Japanese mass media and in particular by Japan's national broadcaster, NHK. Since the 1960s, television has been a fixture of the Japanese household, and NHK's TV news has until very recently been the dominant, and most trusted, source of political information for the Japanese citizen. NHK's news style is distinctive among the broadcasting systems of industrialized countries; it emphasizes facts over interpretation and gives unusual priority to coverage of the national bureaucracy. Krauss argues that this approach is not simply a reflection of Japanese culture, but a result of the organization and processes of NHK and their relationship with the state. These factors had profound consequences for the state's postwar re-legitimization, while the commercial networks' recent challenge to NHK has helped engender the wave of cynicism currently faced by the state. Krauss guides the reader through the complex interactions among politics, media organizations, and Japanese journalism to demonstrate how NHK television news became a shaper of Japan's political world, rather than simply a lens through which to view it.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Pretty Liar: Television, Language, and Gender in Wartime Lebanon - Khazaal, Natalie (Syracuse University Press, 2018)
"Pretty Liar" explores the rise of language and gender politics on Lebanese television to tell the untold story of the co-evolution of Lebanese television and its audiences and how the civil war of 1975-1991 affected that co-evolution. The shift in public interest in television has been widely acknowledged and interpreted within an institutional context as a victory of the neo-liberal entrepreneurship of a new, agile brand over the government inefficiency of Lebanon's national station, Télé Liban. Yet, the role of the Lebanese Civil War in reshaping national television and broadcasting in Arab media following the emergence of the Lebanese Broadcasting Company in 1985 has been unexplored. Based on empirical data and grounded in theory by Arab and global researchers, "Pretty Liar" offers textual analyses of five Lebanese fictional series, three major and several additional periodicals, and nine literary works, and provides context from unscripted interviews with television administrators, anchors, actors, and freelance contributors, print journalists, and audience members. Khazaal seeks to offer new insight into how entertainment television became a site for politics and political resistance, feminism, and the cradle for post-war Lebanon due to the shift in practices and standards of legitimacy. The history of television in Lebanon is not merely the history of technology and business, Khazaal argues, but rather the history of a people and their continuing quest for a responsive television even during times of civil unrest.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Liban (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Global Media: The Television Revolution in Asia - White, James D. (Routledge, 2005)
This book is about the processes of globalization, demonstrated through a comparative study of three television case histories in Asia. Also illustrated are different approaches to providing television services in the world: public service (NHK in Japan), state (CCTV in China) and commercial (STAR TV, based in Hong Kong). Through its focus, Global Media addresses a considerable lacuna in the media studies literature, which tends to have a heavy Western bias. It provides an original addition to the literature on globalization, which is often abstract and anecdotal, in addition to making a major contribution to comparative research in Asia. Finally, it offers a thoughtful causal layered analysis, with a concluding argument in favor of public service television.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Chine (corpus analysé); Hong Kong (corpus analysé); Japon (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Gandhi Meets Primetime: Globalization and Nationalism in Indian Television - Kumar, Shanti (University of Illinois Press, 2005)
Shanti Kumar's Gandhi Meets Primetime examines how cultural imaginations of national identity have been transformed by the rapid growth of satellite and cable television in postcolonial India. To evaluate the growing influence of foreign and domestic satellite and cable channels since 1991, the book considers a wide range of materials including contemporary television programming, historical archives, legal documents, policy statements, academic writings and journalistic accounts. Kumar argues that India's hybrid national identity is manifested in the discourses found in this variety of empirical sources. He deconstructs representations of Mahatma Gandhi as the Father of the Nation on the state-sponsored network Doordarshan and those found on Rupert Murdoch's STAR TV network. The book closely analyzes print advertisements to trace the changing status of the television set as a cultural commodity in postcolonial India and examines publicity brochures, promotional materials and programming schedules of Indian-language networks to outline the role of vernacular media in the discourse of electronic capitalism. The empirical evidence is illuminated by theoretical analyses that combine diverse approaches such as cultural studies, poststructuralism and postcolonial criticism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Politics After Television: Hindu Nationalism and the Reshaping of the Public in India - Rajagopal, Arvind (Cambridge University Press, 2001)
In January 1987, the Indian state-run television began broadcasting a Hindu epic in serial form, The Ramayana, to nationwide audiences, violating a decades-old taboo on religious partisanship. What resulted was the largest political campaign in post-independence times, around the symbol of Lord Ram, led by Hindu nationalists. The complexion of Indian politics was irrevocably changed thereafter. In this book, Arvind Rajagopal analyses this extraordinary series of events. While audiences may have thought they were harking back to an epic golden age, Hindu nationalist leaders were embracing the prospects of neoliberalism and globalisation. Television was the device that hinged these movements together, symbolising the new possibilities of politics, at once more inclusive and authoritarian. Simultaneously, this study examines how the larger historical context was woven into and changed the character of Hindu nationalism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Debating Women’s Issues on Turkish Television: Exploring the Role of Political Power in Women’s Talk - Özcan, Esra (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In this contribution, I provide an in-depth rhetorical and textual analysis of a television debate program broadcast in 2015 on the mainstream television news channel, Habertürk TV in Turkey. The debate brought together women committed to varying political projects, including Kemalism, Islamism, leftist movements, Kurdish women’s movements, and feminism. I find this debate program unique because it took place at a crucial moment in Turkey’s recent history, preceding increasing restrictions on the media that eventually cost more than half of the program participants’ jobs and positions. In my analysis, I focus on how the program’s moderator and the women participants define “women’s issues” in an increasingly authoritarian and conflictual political climate where women are divided with regard to supporting or opposing the Justice and Development Party’s (Adalet ve Kalkınma Partisi—AKP) political program. The results of my analysis show that “sisterhood” does not provide common ground for women in a politically polarized environment and women with more political power dominate the conservation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Introduction: Turkey’s National Television in Transnational Context - Kaptan, Yeşim; Algan, Ece (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The Turkish television industry has undergone great transformation during the past three decades and enjoyed unprecedented success among national and transnational audiences alike. This chapter reconsiders the rise of Turkish television as a global player and an emerging national industry from a new theoretical perspective by situating Turkish television within the contemporary global developments of international television markets and within its own national history, economic, political, and cultural dynamics. By providing different examples of key turning points in its history, we offer a brief overview of TV production, distribution, and reception in Turkey since the beginning of the industry. We also illustrate how societal debates around television content, such as Turkish TV dramas (dizis), have ignited the question of representation and caused a struggle over official narratives, resulting in the entwining of the industry and production processes with politics. In our introductory chapter, we argue that with the increasing demand for content and the expansion of access to online TV platforms, emerging TV industries play an intricate and complex role in reshaping global television flows. Therefore, the case of the Turkish TV industry constitutes a significant example for understanding the current structural transformations in global television and sheds light on the interplay between national and transnational production, distribution, and reception processes.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Tactics of the Industry Against the Strategies of the Government: The Transnationalization of Turkey’s Television Industry - Algan, Ece (The Routledge Companion to Global Television, 2019)
Stuck between the political economy of the larger domestic television production industry and global market imperatives, I argue that Turkey’s TV industry executives and professionals had to develop and implement a number of tactics to achieve a locally based transnational cultural industry able to withstand both global and domestic pressures. In this chapter I identify three main tactics employed by Turkey’s TV industry executives and professionals to combat the socio-economic and political challenges they face: These tactics are: (1) carefully managing the content to skirt government restrictions; (2) adopting the government’s soft power discourse and public diplomacy aspirations by cooperating with government officials and businesses in their cultural promotion and nation-branding efforts; and (3) adapting to global TV trends by undertaking rigorous marketing and branding campaigns. A discussion of these tactics in the Turkish case can help us understand how culture industries in the developing world, which had to integrate into a neoliberal media environment after the 1980s due to market- and state-driven policies propelled mostly by US-based global media giants, negotiate being locally based transnational culture industries in the face of increasingly authoritarian and right-wing domestic political climates.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

TV China: Control and Expansion - Zhu, Ying (The Routledge Companion to Global Television, 2019)
The chapter traces the evolution of Chinese television since 1958 from a state propaganda organ to a profit-generating media juggernaut, with China Central Television (CCTV) as the only network TV responding to both market principles and party directives. Commercialization and marketization played a major role in the rapid development of the Chinese television industry. In recent years China’s TV industry has witnessed the rise of private media companies and the rapid expansion of digital media and the proliferation of over the top (OTT) content. The chapter further provides an overview of China’s overall TV structures and teases out the relationship between CCTV and local stations. The most popular genre on Chinese TV is serial drama, which developed from predominantly single-episode anthology dramas in the 1980s to chiefly multi-episode serial dramas. Talk shows and reality TV became fashionable since the late 1990s.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Chine (corpus analysé); Hong Kong (lieu de production du savoir); _Nettoyé; États-Unis (lieu de production du savoir)

Refashioning Chinese Television Through Digital Fun - Bai, Ruoyun (The Routledge Companion to Global Television, 2019)
This chapter discusses how Chinese television has been refashioned by the digital entertainment industry, and contends that new genres, identities, and representations have emerged in recognition of youths as the most valuable and desirable category of audience. It does so by way of three case studies. The first illustrates the symbiotic relationship between online literature and television drama production, and how the former contributes to the fantastical turn of Chinese television. The second seeks to understand the emergence of new cultural figures of “supreme heroine” and “sweet males” in the context of the rise of female fandom in contemporary Chinese popular culture. The third reveals how traditional television content, or in this case a political drama, may be recreated by online distributors and influencers so as to be aligned with the habits, attitudes, and preferences of the younger audiences. The chapter concludes that to understand contemporary Chinese television culture, the Internet and social media must become an integral component of inquiry because of their powerful remediating role in the public communication of any cultural text.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Identités diasporiques; Canada (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Idol Worship: Ethnicity and Difference in Global Television - Sen, Biswarup (Global Television Formats: Understanding Television Across Borders, 2012)
The worldwide success of the Idol format may not require any explanation. We live under the ubiquitous sign of globalization; and hence it should come as no surprise that mass media— which together constitute an ecumenical vehicle of culture with an insatiable appetite for proﬁt— would generate forms (or formats) of art that travel with ease and are translatable into every context. The reception of these formats is, at one level, as unproblematic as its dissemination. To be global (and who isn’t?) is to be eagerly accepting of certain languages, technologies, discourses and styles. The craze surrounding competitive singing can then be explained as one more instance of borders proving permeable to the formulas of international popular culture. It is my argument that in order to understand the unique valence and signiﬁcance of global formats, we need to go beyond issues of production, distribution and reception, and focus instead on the phenomena that arise from their instantiation . This is so because implementing a format in a speciﬁc context has consequences that are neither written into the “program” nor purely derivable from local conditions. Let me provide an illustration. The call-in talk show has recently become a staple on Indian television. The format and content of these shows would be familiar to most Western viewers— a regular host, one or more “experts” discussing politics and culture, and a ﬁnal segment devoted to phone calls from the public.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Asie du sud (corpus analysé); Inde (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

‘Calling Out Around the World’: The Global Appeal of Reality Dance Formats - Heller, Dana (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, I would like to consider how interactive reality television contributes to the negotiation between national particulars and transnational media ﬂows. Speciﬁcally, I want to look at the successful franchise So You Think You Can Dance , a dynamic global media ﬂashpoint and a remarkably adaptable format that serves as a site of pleasurable and contradictory engagement with the sense of national culture and community that television manufactures. But what makes the show of particular interest to me is that it allows audiences, in an increasing number of television markets around the world, to collectively determine their ideal national performers through a competition that requires mastery of a virtual international smorgasbord of popular dance forms and styles, the vast majority of which originate elsewhere, or from within the national, racial, and ethnic cultures of others. Second, in choosing to examine dance shows, I join with a growing number of scholars who have, over the past 15 years, argued for increased attention to dance as a primary site of knowledge production concerning bodies, identities, and representation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Israël (corpus analysé); Proche-Orient (corpus analysé); Turquie (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)